Electrochemical One-Step Immunoassay Based on Switching Peptides and Pyrolyzed Carbon Electrodes - Park, Jun-Hee; Song, Zhiquan; Bong, Ji-Hong; Kim, Hong-Rae; Kim, Moon-Ju; Choi, Kyung-Hak; Shin, Seung-Shick; Kang, Min-Jung; Lee, Do Young; Pyun, Jae-Chul (AMER CHEMICAL SOC, 2022)
Switching peptides were designed to bind reversibly to the binding pocket of antibodies (IgG) by interacting with frame regions (FRs). These peptides can be quantitatively released when antigens bind to IgG. As FRs have conserved amino acid sequences, switching peptides can be used as antibodies for different antigens and different source animals. In this study, an electrochemical one-step immunoassay was conducted using switching peptides labeled with ferrocene for the quantitative measurement of analytes. For the effective amperometry of the switching peptides labeled with ferrocene, a pyrolyzed carbon electrode was prepared by pyrolysis of the parylene-C film. The feasibility of the pyrolyzed carbon electrode for the electrochemical one-step immunoassay was determined by analyzing its electrochemical properties, such as its low double-layer capacitance (C-dl), high electron transfer rate (k(app)), and wide electrochemical window. In addition, the factors influencing the amperometry of switching peptides labeled with ferrocene were analyzed according to the hydrodynamic radius, the number of intrahydrogen bonds, dipole moments, and diffusion coefficients. Finally, the applicability of the electrochemical one-step immunoassay for the medical diagnosis of the human hepatitis B surface antigen (hHBsAg) was assessed.